ACTIVITIES FOR PHYSICALLY DISABLED IN ISOLATION OF COVID-19 PANDEMIC - Bin Yar, Usama (Journal of University Medical & Dental College, 2021)
Disability is one of a major health problem and billions of disables are suffering in these days of the coronavirus epidemic. As every individual has confined himself in quarantine including disable people. And on the other hand, most importantly people suffering from disabilities are under-going compromised rehabilitation, which ultimately has an adverse effect not only on their health but also on mental health. So, to compensate for their physiological loss, it is necessary to guide the disable community about their health and especially maintaining it through exercise as it is a major healthcare concern nowadays. To overcome such healthcare issues, especially in the case of disabled population, the main aim is to recommend a set of exercises and physical activities to remain fit and active in isolation. The exercises are suggested for amputees, handicapped and bedridden patients. Doing exercise will not only maintain the physical health of disable ones but also improve mental health. Mental health is more important for disable people as they are emotionally sensitive and weak health-wise.